Intracranial artery dissection. (22nd February 2014) - Sikkema, T.; Uyttenboogaart, M.; Eshghi, O.; De Keyser, J.; Brouns, R.; van, J. M. C.; Luijckx, G. J.
<x xml:space="preserve">Abstract</x> The aim of this narrative review is to evaluate the pathogenesis, clinical features, diagnosis, treatment and prognosis of intracranial artery dissection (IAD). IAD is a rare and often unrecognized cause of stroke or subarachnoid haemorrhage (SAH), especially in young adults. Two types of IAD can be identified: a subintimal or subadventitial dissection. It is suggested that a subintimal dissection results in luminal stenosis, thromboembolism and subsequently cerebral ischaemia, whilst a subadventitial IAD could result in the formation of a pseudo‐aneurysm and compression on brainstem or cranial nerves. Rupture of such a dissecting aneurysm causes SAH. The exact cause of IAD remains unknown but several factors are associated with its development. Diagnosis is based on clinical presentation and specific features seen on multimodal neuroimaging. The management of IAD depends on the clinical presentation. In the case of cerebral ischaemia, anticoagulants or antiplatelet agents are used, whilst in the case of SAH endovascular treatment is primarily advocated. Prognosis depends on clinical presentation. Presentation with SAH has a worse prognosis.